2014
DOI: 10.1051/swsc/2014016
|View full text |Cite
|
Sign up to set email alerts
|

The importance of geomagnetic field changes versus rising CO2levels for long-term change in the upper atmosphere

Abstract: The Earth's upper atmosphere has shown signs of cooling and contraction over the past decades. This is generally attributed to the increasing level of atmospheric CO 2 , a coolant in the upper atmosphere. However, especially the charged part of the upper atmosphere, the ionosphere, also responds to the Earth's magnetic field, which has been weakening considerably over the past century, as well as changing in structure. The relative importance of the changing geomagnetic field compared to enhanced CO 2 levels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 46 publications
16
73
0
Order By: Relevance
“…An average daytime h m F 2 is ∼300 km then an h m F 2 decrease is ∼3 km. This is close to the result of model (TIE-GCM) simulations by Cnossen (2014) for a ∼28% increase in CO 2 concentration which gave a fairly uniform decrease in h m F 2 of about 5 km. Assuming that CO 2 increase has started 30-40 years ago one may expect a trend in h m F 2 of 1 km/decade.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An average daytime h m F 2 is ∼300 km then an h m F 2 decrease is ∼3 km. This is close to the result of model (TIE-GCM) simulations by Cnossen (2014) for a ∼28% increase in CO 2 concentration which gave a fairly uniform decrease in h m F 2 of about 5 km. Assuming that CO 2 increase has started 30-40 years ago one may expect a trend in h m F 2 of 1 km/decade.…”
Section: Discussionsupporting
confidence: 88%
“…The same result follows from TIE-GCM model simulations by Cnossen (2014) which show "very clearly how little influence the increase in CO 2 concentration has had on f o F 2 ". Therefore, negative f o F 2 and f o F 1 trends ( Fig.…”
Section: Discussionsupporting
confidence: 67%
“…It should be stressed that there are no direct experimental confirmations that a 20% CO 2 increase in the Earth's atmosphere [ Houghton et al ., ] can explain the observed ionospheric trends. Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model (TIE‐GCM) simulations by Cnossen [] have shown “very clearly how little influence the increase in CO 2 concentration has had on f o F 2 ” and this agrees with theoretical and previous model predictions by Rishbeth [] and Rishbeth and Roble []. The first TIE‐GCM simulations by Rishbeth and Roble [] with doubled CO 2 mixing ratio gave a small f o F 2 decrease, mostly less than 0.5 MHz.…”
Section: Introductionsupporting
confidence: 76%
“…This enhancement in the foE due to the greenhouse effect may lead to a positive trend in the Sq amplitude. The effect of enhanced greenhouse gases on the Sq amplitude was recently simulated by Cnossen (2014), who showed that changes in the ambient magnetic field contribute much more to the long-term trends in the Sq amplitude than enhanced greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%